Molecular analysis of TCGA breast cancer histologic types - Aatish Thennavan; Francisco Beca; Youli Xia; Susana Garcia-Recio; Kimberly Allison; Laura C. Collins; Gary M. Tse; Yunn-Yi Chen; Stuart J. Schnitt; Katherine A. Hoadley; Andrew Beck; Charles M. Perou (Elsevier, 2021)
Summary: Breast cancer is classified into multiple distinct histologic types, and many of the rarer types have limited characterization. Here, we extend The Cancer Genome Atlas Breast Cancer (TCGA-BRCA) dataset with additional histologic type annotations in a total of 1,063 breast cancers. We analyze this extended dataset to define transcriptomic and genomic profiles of six rare, special histologic types: cribriform, micropapillary, mucinous, papillary, metaplastic, and invasive carcinoma with medullary pattern. We show the broader applicability of our constructed special histologic type gene signatures in the TCGA Pan-Cancer Atlas dataset with a predictive model that detects mucinous histologic type across cancers of other organ systems. Using a normal mammary cell differentiation score analysis, we order histologic types into a continuum from stem cell-like to luminal progenitor-like to mature luminal-like. Finally, we classify TCGA-BRCA into 12 consensus groups based on integrated genomic and histological features. We present a rich, openly accessible resource of genomic, molecular, and histologic characterization of TCGA-BRCA to enable studies across the range of breast cancers.